2016
DOI: 10.1017/jfm.2016.431
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion controlled by permeable surfaces: surface properties and scaling

Abstract: Permeable and porous surfaces are common in natural and engineered systems. Flow and transport above such surfaces are significantly affected by the surface properties, e.g. matrix porosity and permeability. However, the relationship between such properties and macroscopic solute transport is largely unknown. In this work, we focus on mass transport in a two-dimensional channel with permeable porous walls under fully developed laminar flow conditions. By means of perturbation theory and asymptotic analysis, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…Webster et al [15] also implemented the same methodology to address effective macroscopic transport parameters between parallel plates with constant concentration boundaries. The presented work can find applications in understanding the chemical reactive transport, [16] describing the transport in a conduit with solute stored in the porous matrix block, [9][10][11][12][13]17] and modelling of non-aqueous phase liquid (NAPL) dissolution. [18] However, the following main features make this study distinct from previous theoretical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Webster et al [15] also implemented the same methodology to address effective macroscopic transport parameters between parallel plates with constant concentration boundaries. The presented work can find applications in understanding the chemical reactive transport, [16] describing the transport in a conduit with solute stored in the porous matrix block, [9][10][11][12][13]17] and modelling of non-aqueous phase liquid (NAPL) dissolution. [18] However, the following main features make this study distinct from previous theoretical studies.…”
Section: Introductionmentioning
confidence: 99%
“…with bandwidths h 1 and h 2 . Software DAKOTA [1] was used to automatize the process of computing the coefficients, basis functions, and truncation parameters appearing in (24). This approach is taken in [47] in the context of independent priors with the aim of computing Sobol' indices for global sensitivity analysis.…”
Section: 2mentioning
confidence: 99%
“…The simulation-assisted approach to the optimal design of porous meta-materials takes advantage of the availability of microscopic (pore-scale) and macroscopic (continuum or Darcy-scale) models, as well as of a bridge between the two provided by various upscaling techniques [52,51,24]. Such a bridge also facilitates analysis of both uncertainty propagation from the microscopic scale to the macroscopic scale and sensitivity of macroscopic material properties to the microscopic ones [47].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a number of studies have experimentally or analytically demonstrated the impact of morphological and topological alteration on, e.g., solute dispersion and fouling at the system (macro-) scale (Maruf et al 2013b;Battiato et al 2010;Griffiths et al 2013;Battiato & Rubol 2014;Rubol et al 2016;Ling et al 2016Ling et al , 2018, ROMs systems are still primarily optimized by trail and error. This is due to the lack of quantitative understanding of the impact of morphological and/or topological modifications on membrane fouling at prescribed operating conditions.…”
Section: Introductionmentioning
confidence: 99%